2018
DOI: 10.1051/e3sconf/20186803011
|View full text |Cite
|
Sign up to set email alerts
|

Control of Chromium Hexavalent (Cr -VI) Pollution on Waste Water in Nickel Ore Extraction Industry with Phytoremediation Technology

Abstract: The issue that surfaces from the digging of limonite and saprolite zones on nickel ore mining is the oxidation of chromium to chromium hexavalent. The aim of this research is to analyze the efficiency level of phytoremediation technology to reduce chromium hexavalent on waste water of nickel ore mining industry. This study was done in situ to observe the potential of Water Lettuce (Pistia stratiotes) using self-designed experimental devices.. This research was divided into three part, such as the variation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Cr3 + treatment of water lettuce showed growth differences that produce a lot of small vegetative plants (tillers). Another research showed that P. stratiotes was able to efficiently reduce Cr6 + in 16 days, thus this plant has a good performance in reducing Cr6 + [20].…”
Section: Discussionmentioning
confidence: 95%
“…Cr3 + treatment of water lettuce showed growth differences that produce a lot of small vegetative plants (tillers). Another research showed that P. stratiotes was able to efficiently reduce Cr6 + in 16 days, thus this plant has a good performance in reducing Cr6 + [20].…”
Section: Discussionmentioning
confidence: 95%